The relationship of smoking duration, sleep disorders, and nutritional status of Indonesian adult men: data analysis of the 2014 Indonesian Family Life Surve - Relawantria Harlianti; Trias Mahmudiono; Dominikus Raditya Atmaka; Siti Helmyati; Mira Dewi; Cindra Tri Yuniar (Health Science Journal of Indonesia, 2021)
Background: In Indonesia, the prevalence of smoking is increasing from year to year and can cause various health problems, such as sleep disorders and affect a person's nutritional status. So, in this study, the relationship between smoking duration, sleep disturbances, and nutritional status in men aged 26–45 years will be investigated using secondary data from the 2014 Indonesia Family Live Survey (IFLS). Methods: The 2014 secondary data from the fifth waves of the IFLS were used for analysis. All 5,379 data of men aged 26–45 years who provided anthropometric, smoking duration, and sleep disorders were included in the study. The Chi-Square test was used to examine the relationship between smoking duration, sleep disorders, and nutritional status in men aged 26 – 45 years. Furthermore, the Multinomial Logistics Regression test is carried out to determine the variables that have the strongest influence. Results: Based on the results of statistical tests conducted, it was found that the majority of respondents had a smoking duration of 11-20 years, of which 27.2% of respondents did not experience sleep disorders and 25.4% had sleep disorders. The nutritional status of respondents with a smoking duration of 11-20 years is normal as many as 35% of respondents and at least 0.5% of respondents have underweight nutritional status with smoking duration <5 years. Furthermore, the test results of the relationship between smoking duration and sleep disturbances obtained p-value = 0.03 and the relationship between smoking duration and nutritional status obtained p-value <0.01. Conclusion: Smoking duration was associated with sleep disorder and overweight nutritional status in men aged 26 – 45 years. Keywords: smoking duration, sleep disorder, nutritional status, tobacco use, sleeping sickness Abstrak Latar belakang: Di Indonesia, prevalensi merokok semakin meningkat dari tahun ke tahun dan dapat menyebabkan berbagai permasalahan kesehatan, seperti gangguan tidur serta mempengaruhi status gizi seseorang. Sehingga pada penelitian ini akan diteliti hubungan antara durasi merokok, gangguan tidur, dan status gizi pada pria berusia 26–45 tahun menggunakan data sekunder dari Indonesia Family Live Survey (IFLS) tahun 2014. Metode: Analisis dari data sekunder gelombang kelima IFLS tahun 2014. Semua 5.379 data pria berusia 26–45 tahun yang memiliki kelengkapan data antropometri, kebiasaan merokok, dan gangguan tidur diikutkan dalam penelitian. Uji Chi-Square digunakan untuk menguji hubungan antara durasi merokok, gangguan tidur, dan status gizi pada pria berusia 26 – 45 tahun. Selanjutnya uji Regresi Logistik Multinomial dilakukan untuk mengetahui variabel yang memiliki pengaruh paling kuat. Hasil: Berdasarkan hasil dari uji statistik yang dilakukan, didapatkan bahwa mayoritas responden memiliki durasi merokok selama 11-20 tahun, dimana sebanyak 27.2% responden tidak mengalami gangguan tidur dan 25.4% mengalami gangguan tidur. Status gizi paling banyak yang dimiliki oleh responden dengan durasi merokok selama 11-20 tahun adalah normal sebanyak 35% responden dan yang paling sedikit sebanyak 0.5% responden memiliki status gizi underweight dengan durasi merokok <5 tahun. Selanjutnya hasil uji hubungan antara durasi merokok dengan gangguan tidur didapatkan nilai p-value=0.03 dan hubungan antara durasi merokok dengan status gizi didapatkan nilai p-value<0.01. Kesimpulan: Durasi merokok berhubungan dengan gangguan tidur dan status gizi overweight pada laki-laki usia 26 – 45 tahun. Kata kunci: durasi merokok, gangguan tidur, status gizi, penggunaan tembakau, penyakit tidur